2021
DOI: 10.1016/j.ijheh.2020.113671
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 antibodies among hospital workers in a German tertiary care center: A sequential follow-up study

Abstract: We sequentially assessed the presence of SARS-CoV-2 IgG antibodies in 1253 hospital workers including 1026 HCWs at the University Medical Center Hamburg-Eppendorf at three time points during the early phase of the epidemic. By the end of the study in July 2020, the overall seroprevalence was 1.8% (n = 22), indicating the overall effectiveness of infection control interventions in mitigating coronavirus disease 2019 (COVID-19) in hospital workers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 16 publications
4
35
0
5
Order By: Relevance
“…Seropositivity either from IgG, IgM or IgA against SARS-CoV-2 was reported at 9.3%. A German-based study by Brehm et al showed a notoriously low seroprevalence in HCW from a tertiary care center in November, with an overall seroprevalence of 1.8% (17). Similar studies have been done in China and India, with antibody positivity rates of 17.14% and 11.1% in July and November respectively, in HCW with negative swab samples (18,19).…”
Section: Seroprevalencementioning
confidence: 68%
“…Seropositivity either from IgG, IgM or IgA against SARS-CoV-2 was reported at 9.3%. A German-based study by Brehm et al showed a notoriously low seroprevalence in HCW from a tertiary care center in November, with an overall seroprevalence of 1.8% (17). Similar studies have been done in China and India, with antibody positivity rates of 17.14% and 11.1% in July and November respectively, in HCW with negative swab samples (18,19).…”
Section: Seroprevalencementioning
confidence: 68%
“…Better knowledge about risk factors for a severe clinical course may have facilitated a better selection of patients requiring hospital admission [ 27 ]. Importantly, various infection control measures, including universal masking of healthcare workers and routine RT-PCR-screening of all patients upon admission, were established at our center [ 28 ], as the knowledge of the particular SARS-CoV-2 transmission patterns increased during the early months of 2020 [ 29 , 30 ]. Thus, the rate of nosocomial infections significantly decreased throughout the study period and vulnerable patient groups were more efficiently protected from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Northern Germany performed in July 2020 observed an overall seroprevalence of 1.8% in 1,253 HCW. They could not detect a significant difference in HCW directly involved in patient care compared to other hospital employees [ 19 ]. A longitudinal study of 679 HCW conducted in Milan, Italy observed similar seroprevalence rates as the current study: March 0.5%; April 5.4%; May 5.9% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%